Influence of coal mining water level decline and soil reconfiguration on groundwater recharge in open pit mining area - SUN Jie (Meikuang Anquan, 2021)
Taking the soil samples collected at Baorixile Open-pit Mine as the research object, based on the relevant soil hydraulics parameters measured in the laboratory, the groundwater level in the field survey and the relevant meteorological data, the soil water migration law was studied in the aeration zone from 1990 to 2016, the feasibility of using soil water flux to estimate precipitation infiltration coefficient is discussed, and the effects of groundwater level decline and soil reconstruction of dump on precipitation infiltration coefficient are analyzed. The results showed that under the condition of natural rainfall, the average soil water flux at 10 m in the steppe area was 20.38 mm, and the average precipitation infiltration coefficient for many years was 0.06; with the increase of groundwater depth, the precipitation infiltration coefficient firstly decreases and then keeps stable at 2 m, that is to say, the drop of groundwater level in the mining area has little effect on the recharge of groundwater by precipitation; at present, the soil reconstruction model of “humus + clay + medium sand” can greatly improve the moisture content of humus and play a positive role in the vegetation restoration of open-pit dump, but to a certain extent, it reduces the infiltration coefficient of precipitation, which makes it unfavorable for groundwater to accept the recharge of meteoric precipitation.